Diagnosis and treatment of thyroblastoma: a case report and review of literature - Chen, Xiting; Xiong, Lijuan; Liu, Hongling; Wang, Haoqiang; Cheng, Donghai; Wang, Wei; He, Wenyuan; Xie, Bo; Zhou, Juan (Frontiers in Oncology, 2025)
Background and objectiveThe diagnosis of thyroblastoma initially identified as a thyroid malignant teratoma was subsequently classified as a distinct entity by the World Health Organization (WHO) in 2022. This classification was based on the observation that the tumor presents with independent primitive multilineage elements and is frequently associated with DICER1 hotspot mutations.The objective of this study was to explore and investigate the clinicopathologic characteristics, molecular features and treatment strategies of patients with thyroblastoma, followed by a review of the previous relevant literature.MethodsThe clinical manifestations, pathological characteristics, molecular features and treatment strategies of the initial case of thyroblastoma pathologically confirmed in China were analyzed.ResultsThe tumor was revealed to have high invasive potential, rapid disease progression, and primitive multilineage elements of pathology, including immature thyroid epithelium, spindled mesenchymal proliferations, and neuroepithelial blastema. Next-generation sequencing (NGS) confirmed the presence of germline DICER1 heterozygous pathogenic mutation at p.G1784* in patient, accompanied by the somatic hotspot mutation at p.E1813D of the RNase IIIb domain. Despite local thyroid tumor resection, the disease continued to progress rapidly. However, chemotherapy with BEP led to a reduction in the tumor. The patient’s progression-free survival (PFS) reached 15 months following the administration of BEP chemotherapy in conjunction with local radiotherapy. The patient ultimately died of cardiac arrest resulting from the progression of the cancer thrombus to the right atrium and right ventricle.ConclusionAlthough thyroblastoma has been treated as a separate entity with its distinctive morphologic and molecular characteristics, its clinicopathological features, diagnosis and treatment methods and prognosis remain poorly understood, which requires more accumulated clinical case data to provide basis for the correct diagnosis and treatment in the future.